DRAMATURGI DALAM IDENTITAS DAN CITRA INFLUENCER KADEER BACHDIM PADA AKUN INSTAGRAM D_KADOOR - Uzda Nabila Shabiriani (Jurnal Nawala Visual, 2021)
Kadeer Bachmid or better known as d_kadoor on Instagram may sound familiar to Javanese people who like to see humorous content on Instagram. Kadeer Bachmid is a celebrity on instagram from Malang, East Java who loves to make funny video content by acting as a fussy mother with a distinctive style of wearing a headscarf, but not taking off her thin mustache and using Javanese language. His expertise in playing the character of fussy mother has made many people like his content while being entertained. But behind it, Kadeer Bachmid is a genuine man and good at reciting beautifully. He has recorded this and put it in his Instagram several times, which is actually the opposite of his video content acting as talkative mothers. Therefore this study aims to analyze the formation of the identity and image of Kadeer Bachmid on the d_kadoor instagram account. The theory used to analyze this phenomenon is the dramaturgy theory popularized by Erving Goffman. This study uses qualitative research methods, namely observation, documentation study, literature study and Focus Group Discussion (FGD) which are very important to determine the design of the research concept.